Execution of Multitarget Node Selection Scheme for Target Position Alteration Monitoring in MANET. (8th June 2022) - Venu, Nookala; Yuvaraj, D.; Barnabas Paul Glady, J.; Pattnaik, Omkar; Singh, Gurpreet; Singh, Mahesh; Adigo, Amsalu Gosu
Abstract : In mobile network, nodes are normally placed in some locations after travelling with various speeds to another location. Packets were broadcast to some location receiver node, but they are moved to another location, due to that node is not able to receive those packets. Attacker node present in routing path should accept those packets, and it acts as original node. Communication privacy is reduced for mobile network. It improves the communication overhead and end to end delay. So, the proposed Enhanced Packet Acceptance for Target Position Alteration (EPATP) technique exactly monitors the target node position, depending on the position to assign the relay node for packet forwarding from sender to target node. Multiaccepter Assigning Algorithm is designed, and if any target node should not receive those packets, it provides another chance for packet receiving by next target node, and it assigns multiple target node for accuracte communication. It reduces communication overhead and end to end delay.